Effectiveness of policy and regulation in European sovereign credit risk markets: A network analysis - Rebekka Buse; Melanie Schienle; Jörg Urban (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
We study the impact of changes in regulations and policy interventions on systemic risk among European sovereigns measured as volatility spillovers in respective credit risk markets. Our unique intraday CDS dataset allows for precise measurement of the effectiveness of these events in a network setting. In particular, it allows discerning interventions which entail significant changes in network cross-effects with appropriate bootstrap confidence intervals. We show that it was mainly regulatory changes with the ban of trading naked sovereign CDS in 2012 as well as the new ISDA regulations in 2014 which were most effective in reducing systemic risk. In comparison, we find that the effect of policy interventions was minor and generally not sustainable. In particular, they only had a significant impact when implemented for the first time and when targeting more than one country. For the volatility spillover channels, we generally find balanced networks with no fragmentation over time.
urn:nbn:de:swb:90-924767
Keywords: G20; G01; G17; C32; C55; G28; 330; Financial Crises; Policy and Regulation; Financial Stability and Systemic Risk in the Eurozone; High-Frequency CDS; Bootstrap Spillover-Measures